Interactive Learning Media on Mathematics Problem Solving Elementary School Students - Eka Hayati; Zulfi Amri (JMEA : Journal of Mathematics Education and Application, 2022)
The method used in this research is the experimental method. The effect of interactive learning media on mathematical problem solving for students with disabilities. The results of the validator's assessment indicate that the interactive learning media is in the very good category with an average score of 4.23 from the maximum range of 5. The practicality test of interactive learning media is indicated by a positive response from teachers and students. The results of the effectiveness test showed that interactive learning media was effective in improving problem solving abilities. This is indicated by the average problem solving ability of students who use interactive learning media to achieve individual and classical mastery. In addition, the average problem solving ability of students who use interactive learning media is better than those who do not use interactive learning media.